Quality of life in gynecologic cancer patients undergoing chemotherapy in Hospital Universiti Sains Malaysia - Rahim, Elmi Farhana Ab (Universiti Sains Malaysia, 2016)
Gynecologic cancers, or cancers that affect a woman's reproductive system, are among the most common cancers in Malaysia. The use of chemotherapy as treatment prove to be promising, it is often associated with adverse effects on quality oflife (QOL) in these cancer patients. Objective of this study was to assess the QOL in gynecologic cancer patients undergoing chemotherapy. A cross-sectional study was used. A total of 70 gynaecology cancer women sampled by non-probability purposive sampling at Hospital USM consented to participate and complete all the European Organization for Research and Treatment of Cancer Quality of Life Questionnaires (EORTC QLQ-C30) components. Data analyses were performed using the Pearson Chi Square, Pearson correlations and one-way ANOV A. A p value :5 0.05 was considered statistically significant. Mean age was 42.79 (SD=12.51) years, with 48.6% ovarian cancer, 28.6% cervical cancer, 12.9% vulva cancer and 2.9% persistent trophoplastic disease. Marital status and occupation were associated with EORTC QLQ-C30 scores in functional (p=0.04) and global QOL (p=0.04). Among symptoms subscales, significant association only existed in loss of appetite (p=0.001) with QOL. Stage of cancer were associated significantly with functional and symptoms scales (p=0.001). Among these patients undergoing one to two chemotherapy cycles, ten (18.2%) had poor QOL scores. Health professionals who care for gynaecology cancer patients need to determine the underlying reasons of poor QOL and initiate observations during multi-professional interventions to provide a better QOL during chemotherapy treatment.